The Role of Job Demands in Moderating the Relationship between Servant Leadership and Job Satisfaction: A Study on Civil Apparatus in Five Major Cities in Indonesia - Sakina Nusarifa Tantri; Shine Pintor Siolemba Patiro; Hendrian Hendrian; Lasando Lumban Gaol (Universitas Pendidikan Ganesha, 2021)
This research aims to reveal the effect of job demands in moderating the relationship between servant leadership and civil apparatus’ job satisfaction. This study involved 200 respondents who spread across Jakarta, Makassar, Medan, Semarang, and Surabaya, using convenience sampling technique. The data of this research were obtained through online surveys. The multiple linear regression analysis was used to test the moderating variable according to the statistical rules. To process the data analysis, we used IBM SPSS 23. The results showed that servant leadership had a positive effect on civil apparatus’ job satisfaction. However, job demands do not moderate the relationship between servant leadership and job satisfaction.